RA09.05: MDM2 AND ERCC1: NOVEL BIOMARKERS TO PREDICT THE RESPONSE TO NEOADJUVANT CHEMOTHERAPY FOR ESOPHAGEAL CANCER PATIENTS. (14th September 2018) - Ito, Ken; Konno, Takuro; Onodera, Yu; Ishida, Hirotaka; Maruyama, Shota; Okamoto, Hiroshi; Sato, Chiaki; Heishi, Takahiro; Sakurai, Tadashi; Taniyama, Yusuke; Kamei, Takashi
Abstract: Background: Neoadjuvant chemotherapy (NAC) by 5-fluorouracil (5-FU) and cisplatin followed by esophagectomy has been established as a standard approach for the patients with clinical stage II/III esophageal squamous cell carcinoma (ESCC) in Japan. However, NAC is not always effective in all these patients, and it is important to identify biomarkers for predicting the response. Therefore, the present study aimed to identify markers for predicting the response to chemotherapy and the clinical outcomes. Methods: This study included 62 ESCC patients who underwent esophagectomy following NAC. We performed immunohistochemical analyses for murine double minute 2 (MDM2), thymidine phosphorylase (TP), dihydropyrimidine dehydrogenase (DPD), and excision repair cross-complementing rodent repair deficiency-1 (ERCC1) in surgical specimens following NAC and assessed the associations of the findings with clinicopathological features in individual patients. Results: The MDM2 status and ERCC1 status demonstrated significant inverse associations with the response to NAC (MDM2: P = 0.025, ERCC1: P = 0.021). In addition, a high TP status in the tumor was significantly associated with tumor differentiation ( P = 0.008), depth of invasion ( P < 0.001), lymphatic invasion ( P = 0.003), venous invasion ( P < 0.001) and tumor stage ( P = 0.006). Moreover, a high DPD status was associated with tumor differentiation ( P = 0.008), depth of invasion ( P < 0.001), venous invasion ( P = 0.003) and tumor stage ( P = 0.007). The TP status also significantly predicted the eventual clinical outcome of patients following surgery. Conclusion: Recently, overexpression of MDM2 has been reported for poor prognosis in patients with ESCC treated by chemoradiotherapy. 5-FU metabolic enzymes, such as TP andDPD, have been investigated for sensitivity to 5-FU. ERCC1, a key component of homologous recombination-based repair of interstrand DNA cross-links, has been reported to predict sensitivity to cisplatin. In our study, MDM2 and ERCC1 immunoreactivity predict chemosensitivity of NAC based on 5-FU and cisplatin. High intratumoral TP status and DPD status are associated with tumor progression and prognosis in ESCC patients receiving NAC. Disclosure: All authors have declared no conflicts of interest.